2021
DOI: 10.1002/ece3.7297
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and habitat attributes associated with the Himalayan red panda in the westernmost distribution range

Abstract: Information on species distribution and habitat use is one of the important aspects of wildlife ecology. Such information is critical for the successful conservation of the species (Braun, 2005). Species distribution models are being widely used in wildlife studies to answer some of those key biological questions (Sinclair et al., 2006).Distribution models establish a quantitative relationship between the relative occurrence of species and their bio-physical and environmental conditions in the landscape (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
8
1
Order By: Relevance
“…The selected model for the cub-rearing season included aspect even though red pandas mostly selected south, southwest, and west aspects throughout the year. This observation contradicts previous findings that red pandas use north, northeast, and northwest aspects ( Yonzon et al 1991 ; Bista et al 2017 ; Shrestha et al 2021 ). We attribute this contrast to underlying variation in micro-habitat in the different areas.…”
Section: Discussioncontrasting
confidence: 96%
“…The selected model for the cub-rearing season included aspect even though red pandas mostly selected south, southwest, and west aspects throughout the year. This observation contradicts previous findings that red pandas use north, northeast, and northwest aspects ( Yonzon et al 1991 ; Bista et al 2017 ; Shrestha et al 2021 ). We attribute this contrast to underlying variation in micro-habitat in the different areas.…”
Section: Discussioncontrasting
confidence: 96%
“…Similarly, we found that the presence of trees, and greater mean tree height use by pandas, reduced stereotypy. Pandas' preferred high elevation habitat is favourable for taller trees 20 , and Shrestha et al found that canopy cover was an important factor in habitats for pandas in the wild 54 . In European zoos, pandas spend 90% of their time off the ground 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, encouraging pandas to spend more of the daytime in feeding and resting by providing proper enrichment will support their natural behaviour. It is notable that these factors are also important habitat attributes for pandas in the wild 54 . Our study is important as the first to provide detailed empirical study of the welfare of captive pandas, and factors influencing it in the Indian subcontinent, where a natural population exists.…”
Section: Discussionmentioning
confidence: 99%
“…Barekot is home to many threatened species, including the Himalayan red panda (Ailurus fulgens fulgens), Himalayan black bear (Ursus thibetanus), musk deer (Moschus spp. ), northern red deer (Muntiacus vaginalis), Himalayan tahr (Hemitragus jemlahicus), common goral (Naemorhedus goral), Himalayan serow (Capricornis thar), and blue sheep (Pseudois nayaur) (Acharya and Paudel 2020;Shrestha et al 2021a;Shrestha et al 2021b). Additionally, the study area is also home to various endangered avian species, such as the Cheer pheasant (Catreus wallichii), Red-headed Vulture (Sarcogyps calvus), and Egyptian Vulture (Neophron percnopterus); the nationally threatened Satyr Tragopan (Tragopan satyra), Bearded Vulture (Gypaetus barbatus), Himalayan Griffon (Gyps himalayensis), and Brown Fish Owl (Bubo zeylonensis); and the Himalayan Monal (Lophophorus impejanus), a Protected bird of Nepal (Paudel & Bhusal 2015).…”
Section: Study Areamentioning
confidence: 99%